Evaluation of marine ecological civilization construction and its spatial correlation network in China’s coastal province from the perspective of land-sea coordination - Gao, Kun; Yu, Lianghong (Frontiers in Marine Science, 2024)
The marine ecological civilization construction (MECC) plays an indispensable role in the development of ecological civilization in China. With the growth of the marine economy, threats to ecological environment have been increasing. From the standpoint of land-sea coordination, this study evaluates the MECC in China's coastal province and employs social network analysis to explore the spatial correlation network structure and radiation capacity. The results show that: (1) The mean value for MECC in China's coastal provinces demonstrates a fluctuating upward trajectory from 2006 to 2021. However, the subsystems exhibit disparate developmental trends, with the pressure subsystem exhibiting a slight decline. (2) While the MECC of all coastal provinces have increased, the MECC of China's coastal provinces exhibits considerable variation, with each facing different development challenges. (3) The spatial correlations of MECC in coastal provinces have become increasingly close, and the spatial correlation network exhibits pronounced geographic proximity characteristics, such as provinces located near Hangzhou Bay and Bohai Bay. In contrast, the spatial correlation of long-distance trans-regional correlation is comparatively weaker. (4) During the study period, there are notable improvements in the MECC radiation capacity of all provinces, particularly in Shanghai, Zhejiang, Jiangsu, and Shandong, which currently rank among the highest in the country. Conversely, the MECC radiation capacity of Liaoning, Hebei, Fujian, and Hainan remains relatively weak.